Incremental predictive value of left atrial strain and left atrial appendage function in rhythm outcome of non-valvular atrial fibrillation patients after catheter ablation. Issue 1 (25th June 2021) - Ma, Xin-Xin; Wang, Aiqing; Lin, Kaibin
Abstract : Objective: The purpose of this study was to develop a non-invasive and convenient nomogram based on speckle tracking echocardiography, left atrial appendage function and clinical factors to predict the risk of atrial fibrillation (AF) recurrence after catheter ablation. Methods: A total of 124 prospectively consecutive patients with AF treated with catheter ablation in our hospital was retrospectively analysis. Baseline echocardiographic parameters were measured by using transthoracic and transesophageal echocardiography before ablation. Multivariate analysis was performed for selecting predictors for a nomogram and internal validation and calibration were evaluated by the bootstep method. Results: During the follow-up of 12±3 months, 41 patients (33.1%) occurred AF recurrence after catheter ablation, while 83 patients (66.9%) had maintained sinus rhythm. Four predictors (AF type, left atrial appendage emptying flow velocity, left Atrial maximal volumes index and global longitudinal strain) with the P<0.5 was selected into the nomogram according to multivariate findings. Internal validation by bootstrapping with 1000 resamples was determined C-index of the nomogram for prediction AF recurrence was 0.901, which showed optimal discrimination and calibration of the established nomogram. Conclusions: Nomogram based on echocardiography and clinical characteristics had good predictive performance for the possibility of AF recurrence, which providing practical guidance for individualised management of patients with AF after catheter ablation.